TransCoding - From `Highbrow Art' to Participatory Culture Social Media - Art - Research - Lüneburg, Barbara (Edition Kulturwissenschaft, 2018)
Between 2014 and 2017, the artistic research project "TransCoding - From 'Highbrow Art' to Participatory Culture" encouraged creative participation in multimedia art via social media. Based on the artworks that emerged from the project, Barbara Lüneburg investigates authorship, authority, motivational factors, and aesthetics in participatory art created with the help of web 2.0 technology. The interdisciplinary approach includes perspectives from sociology, cultural and media studies, and offers an exclusive view and analysis from the inside through the method of artistic research. In addition, the study documents selected community projects and the creation processes of the artworks Slices of Life and Read me.